(untitled) (The Review of Diabetic Studies, 2023)
BACKGROUND: Unlike other strains, spontaneously type 1 non-obese diabetic (NOD) mice experience transient hyperinsulinemia after weaning. The same applies for NOD/SCID mice, which lack functional lymphocytes, and unlike NOD mice, do not develop insulitis and diabetes like NOD mice. AIMS: Given that β-cell stimulation is a natural feature of gestation, we hypothesized that glucose homeostasis is disturbed in gestate pre-diabetic NOD and non-diabetic NOD/SCID mice, which may accelerate the onset of diabetes and increase diabetes prevalence. METHODS: During gestation and postpartum, mice were analyzed under basal feed conditions, and following glucose injection (1 g/kg, i.p.) after overnight fast, using glucose tolerance test (GTT). Glycemia, corticosteronemia, blood and pancreatic insulin, glucagon levels, islet size, and islet morphology were evaluated. Glycemia and mortality were assessed after successive gestations in NOD mice mated for the first time at 2 different ages. RESULTS: 1. Basal glucagonemia rose markedly in first-gestation fed NOD mice. 2. β-cell hyperactivity was present earlier in first-gestation non-diabetic fasted NOD and NOD/SCID mice than in age-matched C57BL/6 mice, assessed by increased insulin/glucose ratio after GTT. 3. Overnight fasting increased corticosteronemia rapidly and sharply in pre-diabetic gestate NOD and NOD/SCID mice. 4. Islet size increased in non-diabetic gestate NOD mice compared with C57BL/6 mice. 5. Successive gestations accelerated diabetes onset, and contributed to increased mortality in NOD mice. CONCLUSIONS: First-gestation prediabetic NOD and non-diabetic NOD/SCID mice exhibited β-cell hyperactivity and deregulation of glucagon and/or corticosterone secretion. This amplified normally occurring insulin resistance, further exhausted maternal β-cells, and accelerated diabetes in NOD mice.